Предмет: Алгебра,
автор: pasha8874
Помогите 13 баллов баллов помогите решить а и б помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
Объяснение:
(m/(mn-n^2) -1/(m-n)) ÷ n/(n-m)=(m/(n(m-n)) -n/(n(m-n)))×(n-m)/n=(m-n)/(n(m-n)) ×(n-m)/n=(n-m)/n^2
(1/(m-n) -n/(m^2 -mn)) ×(n-m)/m=(m/(m(m-n)) -n/(m(m-n))) ×(n-m)/m=(m-n)/(m(m-n)) ×(n-m)/m=(n-m)/m^2
Похожие вопросы
Предмет: Математика,
автор: vitalinasvidka1
Предмет: Биология,
автор: gusevd757
Предмет: География,
автор: hr69cr4hws
Предмет: Математика,
автор: СГтррпьтпшл78765рмр
Предмет: Математика,
автор: SuperStar200